Drawing on the discursive resources from psychological contracts to construct imaginary selves: A psychoanalytic perspective on how identity work drives psychological contracts. (May 2018) - Driver, Michaela
The study contributes novel theoretical perspectives for a more comprehensive and processual understanding of psychological contracts in the context of identity work. It builds on a psychoanalytic, specifically Lacanian, perspective to analyze 106 psychological contract narratives by employees of a wide range of organizations. Based on this analysis, the study suggests that psychological contracts can be understood as providing discursive resources on which narrators draw in complex and non-linear fashion to construct imaginary selves. Their inevitable unsettlement prompts both imaginary and symbolic responses that seem independent of the viability and type of psychological contract narrated. This suggests that identity work drives psychological contracts in surprising ways and empowers individuals as contract and identity-makers. Implications for psychological contract research are discussed.